2021
DOI: 10.1038/s41598-021-92503-6
|View full text |Cite
|
Sign up to set email alerts
|

Simple parameters predicting extrahepatic recurrence after curative hepatectomy for hepatocellular carcinoma

Abstract: Extrahepatic recurrence (EHR) after curative hepatectomy for hepatocellular carcinoma (HCC) is associated with a poor prognosis. We investigated the features of EHR and identified its predictive factors. This retrospective study included 398 treatment-naive patients who underwent curative hepatectomy for HCC at two tertiary hospitals. Multivariate Cox-regression analysis was performed to identify the variables associated with EHR. EHR was diagnosed in 94 patients (23.6%) over a median follow-up period of 5.92 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…EHR of HCC is a well-known predictive marker of poor survival outcomes, and EHR after surgical resection of HCC is deemed to be a pivotal factor for grave prognosis[ 7 , 9 , 17 , 18 ]. In this large-scale 15-year observational study conducted at two academic tertiary hospitals, EHR and early EHR occurred in 17.5% and 9.5% of 779 patients with HCC, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EHR of HCC is a well-known predictive marker of poor survival outcomes, and EHR after surgical resection of HCC is deemed to be a pivotal factor for grave prognosis[ 7 , 9 , 17 , 18 ]. In this large-scale 15-year observational study conducted at two academic tertiary hospitals, EHR and early EHR occurred in 17.5% and 9.5% of 779 patients with HCC, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported simple parameters for predicting EHR after hepatectomy[ 9 ], and in that study, approximately 49.2% of the patients with EHR (31 of 63 patients) showed early EHR and demonstrated poorer recurrence-free survival (RFS) and overall survival rates. There have been many reports regarding the risk factors and predictive models for early recurrence mostly concerning IHR of HCC after surgery[ 10 - 12 ]; however, there are limited data regarding the risk factors and survival outcomes related to early EHR after surgical resection of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…After establishing the diagnosis of HCC recurrence, 43 staging should begin with searching for evidence of extrahepatic disease (present in 12% to 27% of patients) 3 , 4 , 44 since this is largely considered a contraindication to surgical treatment. Some investigators have, however, suggested that even patients with isolated extrahepatic recurrence may still benefit from resection.…”
Section: Staging and Treatment Of Recurrent Hccmentioning
confidence: 99%